TYPES OF AUTOIMMUNE POLYENDOCRINOPATIES IN CHILDREN WITH DIABETES MELLITUS TYPE 1 AND THYROID DISEASE - Adriana, Gherbon (European Scientific Journal, ESJ, 2014)
Background&Aims: If are associated multiple autoimmune endocrine diseases, the term is polyglandular autoimmune syndrome (PAS). The main autoimmune polyendocrinopaties encountered are: PAS I (chronic mucocutaneous candidiasis, chronic autoimmune hypoparathyroidism, and autoimmune Addison disease), PAS II (autoimmune Addison's disease, autoimmune thyroid disease and/or type 1 diabetes) and PAS III (autoimmune thyroid disease + other autoimmune diseases). The purpose of this study is to determine the types of PAS in a group of children with thyroid diseases and diabetes mellitus (DM) type 1. Methods: The studied group was of 83 children with DM type 1 (71 girls and 12 boys), aged between 7 and 17 years. The methods of investigation were represented by clinical, imaging, biochemical, hormonal and immunological parameters. Results: The prevalence of PAS in the study group was: type I – 0%, type II - 6.02 % (80% girls and 20 % boys, p = 0.057, X2 = 3.6) and type III - 59.03 % (85.71% girls and 14.29% boys, p < 0.001, X2 = 50). We don’t find significant differences between boys and girls in the case of PAS type II, but in type III prevailed girls, and the type was III a. Conclusions: The most frequent PAS was type III, subtype III a, follow by type II. Because Addison's disease was asymptomatic, identifying through the presence of specified antibodies, if we have a children with two or more autoimmune disease, we must investigate him for another possible autoimmune disease.